Pelestarian Seni Islam: Analisis Tindakan Sosial Weber - Alfan Faiza Rahman (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2022)
This paper explains descriptively the efforts of preserving Islamic arts, especially the sholawatan carried out by Tim Sholawat Alala al Banjari (the Alala mada’ih team) in Mojo village, Kediri Regency, East Java. This is a qualitative research on the phenomena described at the field through observation and interviews. The phenomenon of art in Islam, especially poetry or mada’ih, is described as experienced quite a long journey since the beginning of the emergence of this religion. It has been acculturated from the beginning as a foreign culture, into a local that highly respect on the beauty of a poem. This paper describes how the activities carried out by the Alala as a social act and how Weber's theory can interpret what the Alala does.